Flora and fauna based on Old Javanese literary reading in the Malang Highlands Region - Suprapta, Blasius (UI Scholars Hub, 2021)
Towards the end of the twelfth century (1104 Ś = AD 1182) until the middle of the fourteenth (1281 Ś = AD 1359), a Hindu-Buddhist civilization, consisting of the Akuwu of Tumapĕl - the kingdom of Siŋhasari – and the kingdom of Majapahit, developed a well-organized social and cultural life in the Malang Highlands Region of Java. This included the management of natural resources, flora and fauna. Although their variety has been well documented in Old Javanese literature and inscriptions, so far there has not been an in-depth study identifying the diversity of flora and fauna of the region during the late Hindu-Buddhist era. This is a study of diverse flora and fauna and how people managed these resources based on reading the source of Old Javanese literature. It begins with library research, followed by diplomatic analysis of various types of flora and fauna in Old Javanese inscriptions, zoological analysis, ethno-zoology, and geographical spatial analysis. The results of the study include the use of various types of flora and fauna in sima ceremonies and everyday agricultural activities. One type of flora, alang-alang (Imperata) which thrives on Gunung Lĕjar, was controlled by the state as it was a fire-risk. Alang-alang was an important thatching material. The trade in endemic plants, herbs, and spices, was protected and regulated by the state. It is also known that the profits from tropical forest management in Bantaran were used for the maintenance of sacred buildings: prāsāda in Hĕmad.